Emotion regulation in first episode adolescent non-suicidal self-injury: What difference does a year make? - Voon, D.; Hasking, Penelope; Martin, G. (Academic Press, 2014)
We examined the roles of cognitive reappraisal, expressive suppression, and rumination in first episode non-suicidal self-injury (NSSI) among adolescents, and the impact of age-related differences in emotion regulation use. Adverse life events and psychological distress played a significant role in NSSI onset. Being male and less use of cognitive reappraisal contributed to NSSI risk but only in regard to 12-month incidence; this effect was not observed when predicting 24-month incidence. Neither expressive suppression nor rumination was related to NSSI onset in our sample. Age-related differences in emotion regulation were found, but did not modify the above relationships. Findings hint at the possible impact of developmental changes in adolescents' cognitive-emotional processing and their subsequent risk of NSSI. Results support further investigation into prevention and early intervention initiatives aimed at assisting adolescents cope with acute life stressors to prevent/delay first episode NSSI.